Global community : global security - Osborne, Randall E.; Kriese, Paul, 1943- (Value Inquiry Book Series, 2008)
Global security cannot be achieved until people view the world as a global community. Until such time, differences will continue to be perceived as threatening. These perceived "threats" are the primary threat to global security. This volume proposes methods for minimizing the "us versus them" mentality so that we can build a sense of global community.